Thermal optimisation of the stator vent design for a synchronous generator - Bersch, Kevin (2019)
An appropriate cooling of electrical machines is essential for safe, reliable and efficient operation and to address the growing demand for highly power-dense machines. Conventional thermal design optimisation procedures have traditionally relied on simple analytical correlations, which are not well suited to investigate complex and novel designs. Computational Fluid Dynamics (CFD) enables a more accurate prediction of fluid flow and heat transfer. But to date, the high complexity of the geometry, mesh and solver setup have required the model setup to be updated manually when the machine design is changed.